2021
DOI: 10.3389/fonc.2021.647559
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Modulates Cellular Metabolism Through Histone Lactylation-Mediated Gene Expression in Non-Small Cell Lung Cancer

Abstract: Lactate has been observed to fuel TCA cycle and is associated with cancer progression in human lung cancer, the leading cause of cancer deaths worldwide, but the effect of lactate on lung cancer metabolism is rarely reported. In this study, disordered metabolism in non-small cell lung cancer was demonstrated by increased G6PD and SDHA protein levels via immunofluorescence, and up-regulated lactate dehydrogenase was found to be associated with poor prognosis. Then flow cytometry and Seahorse XFe analyzer were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 28 publications
3
80
0
Order By: Relevance
“…reported lactate-derived histone lysine lactylation (Kla) as a novel post-translational modification (PTM) that stimulated gene transcription in macrophages ( Zhang et al., 2019a ). The functions of histone Kla were then explored in mouse embryo fibroblasts (MEFs) ( Li et al., 2020a ), ocular melanoma cells ( Yu et al., 2021 ), and non-small cell lung cancer (NSCLC) cells ( Jiang et al., 2021 ); these studies indicated that Kla has important effects in regulating pluripotency and oncogenesis. Few studies have focused on Kla of non-histone proteins, although such studies have been conducted in Botrytis cinerea and Oryza sativa ( Gao et al., 2020 ; Meng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…reported lactate-derived histone lysine lactylation (Kla) as a novel post-translational modification (PTM) that stimulated gene transcription in macrophages ( Zhang et al., 2019a ). The functions of histone Kla were then explored in mouse embryo fibroblasts (MEFs) ( Li et al., 2020a ), ocular melanoma cells ( Yu et al., 2021 ), and non-small cell lung cancer (NSCLC) cells ( Jiang et al., 2021 ); these studies indicated that Kla has important effects in regulating pluripotency and oncogenesis. Few studies have focused on Kla of non-histone proteins, although such studies have been conducted in Botrytis cinerea and Oryza sativa ( Gao et al., 2020 ; Meng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…HCAR1 is highly expressed in breast cancer. To determine whether Hcar1 was expressed in cancer cells of solid tumours, whose interior are hypoxic and shows more lactate accumulation (20,21), Hcar1 mrna levels were analyzed in various cancer cell lines. it was found that Hcar1 was expressed in tongue, lung, breast, bladder, pancreatic, hepatocellular, colorectal, cervical and epidermal carcinoma cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of the current study was to determine if lactylation was present in human skeletal muscle utilizing a pan anti-Kla antibody commonly used to identify lactylation in other cell types ( Zhang et al, 2019 ; Chu et al, 2021 ; Cui et al, 2021 ; Hagiharai et al, 2021 ; Jiang et al, 2021 ; Meng et al, 2021 ). The confirmation of lactate-induced lactylation in human skeletal muscle advocates for future research to identify the specific proteins that undergo lactylation.…”
Section: Discussionmentioning
confidence: 99%